Implications of Zimbabwe’s fast-track land reform programme on its relations with the SADC States - Kasirowori, Walter (Midlands State University, 2020)
The research study sought to analyse the implications of Zimbabwe’s Land Reform Programme on its Relations with the SADC states as well as to proffer scholarly and policy recommendations that will lead to sound SADC relations of regional integration. A qualitative approach was adopted, utilising interviews and questionnaires to gather primary data. Secondary data was obtained from several publications, journals and government reports and reputable media publications. The study was prompted by increasing concern over the manner in which the FTLRP was conducted in Zimbabwe as a domestic issue with potential to influence foreign relations, especially with neighboring countries in the SADC region. The FTLRP followed several attempts to correct the colonial injustices over land access and ownership as the previous arrangement favoured the white, colonial settlers. Several initiatives were contemplated including the passing of the Land Tenure Act of 1978 which repealed the Land Tenure 1969 and the Lancaster House Agreement in 1979 through the ‘willing-buyer-willing-seller’ arrangement. These initiatives proved too slow, or rather delayed in rectifying the land issue which seemed to be the major concern for the Liberation struggle. Consequently, Zimbabweans engaged in the FTLRP through land invasions by forcibly taking land from whites, a move which has had far reaching implications on Zimbabwe’s relations with her neighbours in the SADC. While some SADC member states like Namibia applauded the FTLRP in Zimbabwe, other members like Botswana out rightly differed in opinion. Such a situation suggests divided opinion within the SADC region following the Zimbabwean FTLRP which threatens relations amongst member states. Zimbabwean exports to SADC countries, mainly in the form of agricultural produce dwindled. Also, there was over supply of labour as previously farm workers were left without employment; hence many people migrated into neighboring countries in search of employment. While other countries like Namibia supported the approach taken by Zimbabwe, others were opposed to this move, especially Botswana. However, despite such differences in ideology and perceptions, the SADC countries continued in their efforts to preserve peace and security in the region. The FTLRP was a domestic policy with the objective of correcting the crooked colonial land discrepancies that led to the subjugation of the majority black population. The FTLRP was a vi bilateral issue between Zimbabwe and Britain that influenced political, economic, military/security and social implications on SADC relations. Domestic policy implementation can have regional or international socio-political, economic and security implications; therefore, the objectives of the study were to analyse the implications of Zimbabwe’s Land Reform Programme on its Relations with the SADC states; to examine the effects of Zimbabwe’s land reform on the political economy of the SADC Member States and to proffer scholarly as well as policy recommendations on how domestic Fast-track Land Reform Programmes can be done in a way that will lead to sound SADC regional integration.